SCCS evidence to BEIS on Greenhouse Gas Removals - SCCS (SCCS, 2021)
SCCS' response to a call for evidence from BEIS on greenhouse gas removal (GGR) technologies.
SCCS' response to a call for evidence from BEIS on greenhouse gas removal (GGR) technologies.
Keywords: CCS; carbon capture and storage; greenhouse gas removals; GGR; evidence